Apoio familiar, sintomas depressivos e consumo de substâncias psicoativas em adolescentes da cidade de Recife. - Dias, Catarina Irene Rodrigues (2023)
Adolescent development is contextual and historical, and this transition is permeated by multiple transformations at the biopsychosocial and behavioral levels, assuming varied forms in different social, cultural, and economic contexts. Likewise, adolescence is considered a phase that involves affective, family and social questions and that the emotional needs and conflicts of this period can influence risky or dangerous behavior. Consequently, contributing to the vulnerability of the use of psychoactive substances by adolescents, generating permanent consequences or fatalities, thus making them the largest group with causes of death that can be avoided. In view of this, the objective of the present study was to analyze the relationship established between family support, depressive symptoms and consumption of psychoactive substances (PAS) perceived by adolescents. Specifically, to contextualize the importance of the family in the adolescent's development; characterize the factors that contribute to the development of depression and address the contexts of vulnerability to the consumption of SPA's in this phase. Still, to map the sociodemographic data and the indicators of family support and behaviors related to the consumption of SPA's, to track depressive symptoms, to correlate the indicators of family support, depressive tendency and consumption of SPA's and, finally, to analyze the influence of the variables perceptions of family support, depressive tendency and consumption of SPA's in the development of adolescents. The sample was stratified from the six Political-Administrative Regions (RPA's) of the City of Recife. Collectively, 372 students from public schools, aged 13 and 15, of both sexes, participated. Items from the Health Behavior in School-aged Children (HBSC) protocol related to sociodemographic data, family support, substance use and the Children's Depression Inventory (CDI) were used. Results: The predominant sociodemographic profile was 15-year-old students (63.2%), female (61.3%), enrolled in the 1st year of high school (48.1%) and self-declared brown (50.3%). It was possible to verify the relationship between the perception of family support, depressive tendency and consumption of psychoactive substances in adolescents. The analysis of correlations (Pearson's r) indicated the occurrence of significant relationships between the total score of the perception of depressive tendency and gender (r = 5.42; p < 0.01), which confirms what was previously observed in the comparison of means in terms of greater perception of depressive symptoms in female adolescents. It also demonstrates that greater dialogue (r =-0.389, p<0.001) and family support (r =-0.378, p<0.001) have a greater impact on the reduction in the CDI, as well as the increase in the perception of parental supervision (r =- 0.218, p<0.001) and perception of feeling like talking about their concerns (r =-0.127, p=0.015), indicate a reduction in depressive symptoms. And, the total score of the perception of depressive tendency showed a significant relationship with alcohol consumption (r=2.69, p=0.012) and a borderline significant relationship for tobacco use (r = 3.85, p < 0.051) with tendency to association with increasing sample size. Finally, the significance of the correlation between the total CDI score and the total score for marijuana use (r=11.0, p<0.001) is highlighted. These results reinforce the evidence that the greater perception of depressive symptoms is in females, in adolescents who perceive themselves with less dialogue and family support, as well as in the group of adolescents who consume alcohol and marijuana. Immediate interventions are considered important considering depressive symptoms and alcohol consumption by female adolescents.